S245. BRAIN CONNECTIVITY CHANGES AFTER COGNITIVE REMEDIATION: A RESTING-STATE STUDY. (18th May 2020) - Penadés, Rafael; Segura, Barbara; Inguanzo, Anna; Garcia-Rizo, Clemente; Catalán, Rosa; Masana, Guillem; Bernardo, Miquel; Junqué, Carme
Abstract: Background: Some studies have showed how Cognitive Remediation is able to improve activation patterns in the frontal lobe. However, only few data on neuroconnectivity has been reported yet. Resting-state fMRI approach seems to be a promising methodology with potentiality for testing neuroconnectivity. Methods: A randomized and controlled trial was carried out with three groups: patients receiving Cognitive Remediation Therapy (CRT), patients receiving Social Skills Training (SST) as an active control, and a healthy control (HC) group. A resting-state fMRI data was acquired in part of the sample (n = 26 patients, n = 10 healthy controls) of a partner study (NCT 02341131). A data-driven approach using independent component analysis (ICA) was used to identify functional brain networks, which were compared between groups and group per time using a dual-regression approach. Results: ICA results revealed reduced functional connectivity between patients and controls in sensorimotor, basal ganglia, default mode and visual networks at baseline (p<0.05 FEW-corrected). After treatment, time per group analyses evidenced increased connectivity in sensorimotor network. Furthermore, group comparison at follow-up showed similar connectivity patterns between patients and healthy controls in sensorimotor network, but also in default mode and basal ganglia networks. Discussion: Cognitive remediation could be able to strengthen some aspects of brain connectivity networks. Our data could be in line of the hypothesis of disconnectivity in schizophrenia. However, cognitive remediation but also social skills training seemed to be able to induce detectable changes in brain functioning in terms of restoring some aspects on the connectivity pattern.